Advancing Public Health Nutrition Teaching and Learning Forum Report : Curriculum Renewal in Public Health Nutrition (CRIPHN) : Thursday 24th and Friday 25th November 2011, The Old Woolstores Apartment Hotel and Conference, Hobart. - Yeatman, Heather; Hughes, Roger; Begley, Andrea; Schubert, Lisa; Williams, Lauren (Office for Learning and Teaching, 2012)
Forum report from the second stage of a project that used a consensus-based approach to develop academic standards to support the emerging discipline and workforce of public health nutrition (PHN). There is a need for a current academic discipline base and pedagogy for the education of professionals who are able to address contemporary food issues. A modified Delphi methodology was used to reach consensus on PHN academic standards. The project developed a competencies framework, including competency units, elements and performance/assessment criteria (consistent with competency frameworks used by professional disciplines). These codified and made explicit the knowledge, skills and attitudes required to perform effectively the work required of a public health nutrition practitioner, from graduate entry to advanced practitioner at both undergraduate and postgraduate levels. A national forum was conducted to disseminate and operationalise the academic standards. The process formed the first phase in curriculum renewal in PHN, to be articulated at national and international levels.